THE DIFFERENCES OF DEPRESSIVE SYMPTOMS BY GENDER IN PEOPLE WITH PSORIASIS - Fransiska, Annisa; Husada M, Surya; Effendy, Elmeida (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of the study were to determine the differences of depressive symptoms by gender in people with psoriasis. Methods: This study was a comparative analytical study with cross-sectional approach, the sampling techniques using non-probability sampling with consecutive sampling techniques types. Place of study: Psoriasis foundation Medan research time: January 2014â€“March 2014. Every patient who meets the criteria of psoriasis vulgaris patients aged 16â€“60 years, disease duration >6 months, able to read and write, cooperative and willing to participate in the study, did not suffer severe medical illness, did not suffer from other mental disorders, and not using illicit substances included in the study, and then, to assess depressive symptoms using a questionnaire beck depression inventory-II. Results: A total of 80 patients were evenly split into groups of men and women have the highest life characteristics at 16â€“38 years (55% and 72.5%). Highest education in higher education both 95% and the severity of depressive symptoms was also a lot of artifacts on minimal depressive symptoms (82.5% and 72.5%). Cross-table test showed no significant difference in depressive symptoms between male and women (p>0.05). Conclusion: Overall in people with psoriasis there was no significant difference of depressive symptoms by gender for the entire data.